AI-BASED CLAY ANIMATION AS DIGITAL LITERACY IN SRIWIJAYA HISTORY AND CULTURE LEARNING - Raini, Yeni; Suartika, Ika; Nurudin Fadillah, Apik (EDUCATE : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop and test the feasibility of AI-based Clay Animation media as a digital literacy media for learning Sriwijaya history and culture using the Hannafin and Peck Development Model which includes three main stages, namely: needs assessment, design, and development and implementation accompanied by a continuous evaluation and revision process at each stage. The resulting product is an AI-based Clay Animation media that integrates historical narratives, cinematic visuals, cultural values, and digital literacy elements so that it is able to present an authentic and meaningful learning experience. Data collection instruments are in the form of Literature Studies, Observations, Interviews and Documentation which are then processed using Quantitative and Qualitative analysis techniques. The product validation carried out obtained Very feasible results with a score of 94% from Material Experts, 92% from Media Experts, 90% from Language Experts and 93% from Learning Design Experts. Meanwhile, the trial involved audiences to assess feasibility, resulting in a score of 92.25%, practicality of 93%, and media effectiveness, as seen from the average posttest score of 86.9, compared to the average pretest score of 63.8. The N-Gain result was 0.64, categorized as Medium-High. The research output was a valid, practical, and effective digital learning animation that improved historical understanding, digital literacy skills, and student awareness of the preservation of Sriwijaya’s cultural heritage.